Applying metalytics to measure customer experience in the metaverse - Bathla, Devesh 1986-; Amandeep Singh 1982- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series, 2022)
"This book presents research chapters on emerging trends into the metaverse that is introducing new technologies and preparing users to interact within the new dimension of the virtual universe"